A Critical Analysis of China’s Listed Companies’ Defensive Capability against Hostile Bids - Zhang Zhe (Eximia, 2025)
Takeover activities in China have experienced rapid development because of the reform of the financial market. Though the authority has achieved considerable progress in attempting to establish a coherent and predictable regulatory regime for takeover activities in the last three decades, the current framework is extremely complicated and fragmented. After analyzing the nature of the non-frustration rule from the available defenses in theory and practice, and considering the defensive capability of listed companies under China’s company law without the non-frustration rule, it is obvious that there are many problems arising from the weak defensive capability of China’s listed companies. For example, fund management benchmarking transmits outside short-termism into the board and the bargaining power of the management to negotiate a better price for its shareholders is impeded. Especially when the asset acquisition involves intangible assets such as patented technologies and trademarks. The article submits that the non-frustration prohibition should be abolished to enhance the defensive power. Moreover, further interpretations about the demarcation of the corporate power between shareholders and directors should be contemplated to clarify the range of directors’ discretions concerning defensive measures.